1978
DOI: 10.1159/000241080
|View full text |Cite
|
Sign up to set email alerts
|

The Postnatal Development of Rats Born Preterm and Postterm

Abstract: Groups of 3 preterm (duration of gestation 22 days), 3 term (23 days), and 3 postterm (24 days) rats have been fed together by 1 mother rat. The postnatal growth of liver, brain, heart and kidney has been studied up to the 30th day of life. The postnatal loss of water shows good correlation with the maturation of each organ. The postnatal loss of water is marked in brain and kidneys, but only slight in liver and heart. The pronounced growth spurt of the brain at the about 10th day of life is probably due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…tional to the litter size (Widdowson and McCance, 1960;Heggeness et al, 1961;Kumaresan et al, 1967;Priestnall, 1974;Galler and Turkewitz, 1975;Buhrdel et al, 1978;Kreckmann et al, 1994). For example, we have found that for rats commonly referred to as Charles River CD rats (cesarean-derived, an offshoot of Sprague-Dawley rats) used in our laboratories (maternal body weight in the range 300-400 g), the average pup weight at weaning for a 5-member unculled litter is 68 g, compared with only 40 g for an unculled litter size of 18 (Table 1).…”
Section: A Effect Of Litter Size On Postnatal Growth Of Rodentmentioning
confidence: 99%
“…tional to the litter size (Widdowson and McCance, 1960;Heggeness et al, 1961;Kumaresan et al, 1967;Priestnall, 1974;Galler and Turkewitz, 1975;Buhrdel et al, 1978;Kreckmann et al, 1994). For example, we have found that for rats commonly referred to as Charles River CD rats (cesarean-derived, an offshoot of Sprague-Dawley rats) used in our laboratories (maternal body weight in the range 300-400 g), the average pup weight at weaning for a 5-member unculled litter is 68 g, compared with only 40 g for an unculled litter size of 18 (Table 1).…”
Section: A Effect Of Litter Size On Postnatal Growth Of Rodentmentioning
confidence: 99%